A Correlational Study on Oral Health and Oral Health-Related Quality of Life among Older Adults Attending Dental Outpatient Department of Selected Community Health Center of D and Nh - Parmar, Dharini; Sharma, Priya; Malik2, Sujeeta (International Journal of Nursing Research, 2023)
Introduction: Oral health is a key indicator of overall health, well-being, and quality of life (QoL). It encompasses a range of diseases and conditions that include dental caries, periodontal disease, tooth loss, oral cancer, oral manifestations of HIV infection, and orodental trauma. Aim: The aim of the study was to correlate oral health and oral health-related QoL among older adults attending dental outpatient department of selected community health center of Dadra and Nagar Haveli. Materials and Methods: Survey approach was used to determine the correlation between oral health and oral health-related QoL among older adults. A descriptive correlational study design was adopted for conducting the study. The sample for the study was 165 older adults aged 50 years and above who have oral diseases/problem which were selected by non-probability purposive sampling technique. Structured Questionnaire on Demographic characteristics was developed by investigator for the purpose of collecting background information of the sample. Observational checklist was used to assess oral health status of older adults. Oral health impact profile (OHIP-14) tool was adopted to assess behavior on oral health status. Results: A total of 165 subjects were interviewed and examined. All were favorable to participate in this research study on level of oral health. There is low impact profile on level of oral health-related QoL. There is highly significant (P < 0.001***) correlation between oral health and oral health-related QoL among older adults with r-value of 0.4176. Conclusion: Hence, the study concludes that OHIP-14 was highly significance correlation between oral health and oral health-related QoL among older adults.